Analisis Pelanggaran Sila Pertama Pancasila Dalam Kontroversi Tayangan Trans7 Yang Dianggap Menghina Kiai dan Pesantren - Ismi Salsabila Daulay; Naufal Rizki; Hanna Devana; M.Dinar Nazwi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The value of Almighty Godhead in the first principle of Pancasila demands respect for religious figures and institutions. This research analyzes the violation of this value in the case of the Trans7 program, 'Xpose Uncensored,' aired on October 13, 2025, which was deemed to belittle the Lirboyo Islamic Boarding School and one of its caretakers, KH Anwar Manshur. The content included narration suggesting the giving of envelopes to the Kiai and discussing a luxurious lifestyle. This qualitative case study utilizes literature review from official documents and credible news sources. The analysis concludes that the broadcast violated the value of Almighty Godhead by diminishing the dignity of religious figures and institutions, and failed to meet the principles of the Broadcast Behavior Guidelines and Broadcast Program Standards (P3SPS) regarding religious sensitivity. This violation had a significant impact, causing social unrest and potential conflict, supported by strong condemnations from various groups such as LBH Ansor, Himasal, PW GP Ansor Jatim, and PBNU. Therefore, media is urged to strengthen internal oversight and uphold balanced broadcasting ethics.